Pengembangan Protokol TEBAS (Teliti, Evaluasi, Blokir, Amankan, Sampaikan) sebagai Kerangka Mitigasi Serangan Social Engineering Berbasis Komunitas - Khairul; Ade Surya Bakti Pane; Harmiati Bungsu Bangun; Astri Mutia Rahma; Erbin Sitorus (CV. Hawari, 2026)
In the contemporary cybersecurity landscape, the attack paradigm shift from exploiting technical vulnerabilities to manipulating human psychology (social engineering) has reached a critical level. The 2024 and 2025 annual reports from various global and national security authorities indicate that traditional defense mechanisms centered on the technical perimeter are no longer sufficient to stem the tide of attacks targeting the user's cognitive layer. This paper proposes the development and formalization of a new mitigation protocol, TEBAS (Research, Evaluation, Block, Secure, Deliver). This protocol was designed using the Design Science Research (DSR) methodology to address the specific needs of Indonesia's digital ecosystem, characterized by a highly communal culture but facing a significant digital literacy gap. TEBAS integrates human-centric cybersecurity principles with global standard frameworks such as the NIST Cybersecurity Framework 2.0, but is adapted into operational procedures that can be implemented by individuals and communities. Through an in-depth analysis of current attack vectors such as Quishing (QR Code Phishing) and Deepfake Vishing, and validation using a modified Delphi method, this study demonstrates that TEBAS offers a holistic approach that focuses not only on individual detection but also on collective resilience through a community-based intelligence-sharing mechanism (